(untitled) (Scientific Journal of Research Studies in Future Civil Engineering, 2026)
This article presents a critical synthesis of advanced seismic engineering strategies to enhance the resilience of multi-story steel buildings. It examines the shift in seismic design from traditional collapse prevention to prioritizing post-earthquake functionality and operational continuity. Through a focused review of column base behavior, this work addresses a significant gap in conventional design by synthesizing innovative solutions. It details the management of complex structural behaviors such as drift concentration, P-delta effects, and biaxial seismic response, along with their practical implications. The paper discusses low-damage self-centering systems and the Continuous Column Concept (CCC), explaining how column base flexibility can localize inelastic deformation to replaceable components and minimize residual drifts. It highlights significant challenges in practical application, including the need for improved modeling accuracy of column base behavior under multiaxial loading and for accounting for scaling effects in tall buildings. The review concludes by identifying key directions for future research, advocating for refined multi-axial demand modeling, standardization of new design methods, and the development of practical design tools to bridge the gap between cutting-edge research and current engineering practice, ultimately guiding the pursuit of truly resilient urban infrastructure.